Efektivitas Suplementasi Tepung Daun Kelor dan Bee Bread Terhadap Kadar Hemoglobin, Hematokrit Remaja Putri Anemia - Sri Hardiyanti (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: anemia is still a health problem moringa plant in Latin known as Moringa Oleifera Lam is one type of plant that contains high iron. Objective: To determine the effectiveness of supplementation of Moringa leaf flour capsules and bee bread on hemoglobin and hematocrit levels of anemic adolescent girls. Method: Randomized Controlled Trial (RCT). The subjects of the study were anemic adolescent girls, 13 people in the intervention group (giving supplements of Moringa leaf flour capsules and bee bread), and 11 control groups (giving supplements of Moringa leaf flour capsules and placebo) according to the inclusion and exclusion criteria. Characteristic data was measured using a temporary questionnaire to assess changes in hemoglobin and hematocrit levels, pre-and post-supplementation blood samples were tested. Data analysis using Chi-Square, Dependent, and Independent t-test. Results: The increase in hemoglobin levels was greater in the intervention group (mean difference 1.72) compared to the control group (mean difference 1.15). Meanwhile, the hematocrit level experienced a greater decrease in the control group (mean difference 3.27) than the intervention group (mean difference 2.78). Conclusion: there is no significant difference in the comparison of hemoglobin and hematocrit values ​​between the intervention and control groups after supplementation (posttest)